Combined lateral femoral epicondylar osteotomy and a submeniscal approach for the treatment of a tibial plateau fracture involving the posterolateral quadrant. Issue 2 (February 2015) - Yoon, Yong-Cheol; Sim, Jae-Ang; Kim, Dong-Hyun; Lee, Beom-Koo
Abstract: Exposure of a tibial plateau fracture involving the posterolateral quadrant is challenging, and several approaches for treating these fractures have been introduced. However, these approaches may have limited applicability, and they can potentially cause neurovascular, musculotendinous, or ligamentous injury of the posterolateral corner. Lateral femoral epicondylar osteotomy has been used for meniscal transplantation, total knee arthroplasty, and the treatment of posterolateral articular disorders of the femur and tibia. We encountered a case of a tibial plateau fracture involving the posterolateral quadrant without an anterior-extending fracture line. We successfully exposed, reduced, and fixed the fracture using combined lateral femoral epicondylar osteotomy and a submeniscal approach. This combined modality can be used as an alternative surgical technique for the treatment of tibial plateau fractures involving the posterolateral quadrant.